EVALUASI PROGRAM BIMBINGAN BELAJAR DAN KONSELING DALAM MENCEGAH KEKERASAN SEKSUAL DI MTS NEGERI 1 PAMEKASAN - Dyah Ayu Puspita Dita Admaja; Rusdiana Navlia (MPI STAI Sangatta Kutai Timur, 2025)
Tutoring and counseling have an important role in providing guidance and helping to solve problems that occur in students. The tutoring and counseling program at MTs Negeri 1 Pamekasan has a very high effectiveness in preventing sexual violence. The purpose of writing this article is to describe and analyze the effectiveness of the tutoring and counseling program at MTs Negeri 1 Pamekasan in preventing sexual violence, as well as to identify factors that influence the success of the program. The research method used is a descriptive qualitative approach with data collection techniques in the form of direct interviews with informants and data analysis using source triangulation. The results of the study show that the tutoring and counseling program at MTs Negeri 1 Pamekasan has a vital role in helping students solve problems and form good character; the program is very effective in providing education about the dangers of sexual violence; there are several obstacles faced in preventing sexual violence that can hinder the success of the program; collaboration with stakeholders and authorities is very important in supporting the success of the program; and student behavior can change when faced with a problem, such as changes in behavior, physical, emotional, and academic potential.